2008
DOI: 10.1080/07315724.2008.10719718
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Geriatric Nutritional Risk Index and Total Lymphocyte Count with Short-Term Nutrition-Related Complications in Institutionalised Elderly

Abstract: In the institutionalised elderly patients, GNRI confirmed its predictive value even for short-term health complications, particularly when death was considered. However, the use of TLC might improve the evaluation of nutritional risk and the identification of patients at risk of infections. Nutrition study should be considered to confirm possible risk reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 39 publications
0
29
0
2
Order By: Relevance
“…Thus, performing more assessment methods, and combining their results, would probably allow a better evaluation and categorization of the patient. This has been recently pointed out for the GNRI [29,30]. Particularly, we observed that the periodical documentation of changes in overall (percentage of food consumed to that delivered) and protein (g/kg per day) intakes might improve the recognition of initial stages of muscle dysfunction in institutionalized elderly not suffering from acute complications [29].…”
Section: Geriatric Nutritional Risk Index In the 'World Of Screening mentioning
confidence: 69%
See 2 more Smart Citations
“…Thus, performing more assessment methods, and combining their results, would probably allow a better evaluation and categorization of the patient. This has been recently pointed out for the GNRI [29,30]. Particularly, we observed that the periodical documentation of changes in overall (percentage of food consumed to that delivered) and protein (g/kg per day) intakes might improve the recognition of initial stages of muscle dysfunction in institutionalized elderly not suffering from acute complications [29].…”
Section: Geriatric Nutritional Risk Index In the 'World Of Screening mentioning
confidence: 69%
“…Thus, one might have assumed that it was more suitable for a subacute care setting but a preliminary investigation tested and demonstrated its prognostic value (1-month risk of death) also in acutely hospitalized patients [36]. Thereafter, different studies have suggested an interesting application in nursing homes [34] not only when addressing the association with prognostic indicators, such as muscle dysfunction [28,29], but also when seeking for both mid (6 months) and long-term (>3 years) outcome prediction [30][31][32][33]. Moreover, patients with pressure ulcers frequently appear characterized by low GNRI values (32% with GNRI < 82 or 85% with GNRI < 92) (Cereda et al, unpublished data).…”
Section: Geriatric Nutritional Risk Index and Settingmentioning
confidence: 97%
See 1 more Smart Citation
“…However, despite its frequent use, albuminemia remains an unreliable indicator of the nutritional status, because it may be more closely related to inflammation or the hydration status than to malnutrition. Recently, the Geriatric Nutritional Risk Index (GNRI), a new prognostic index of nutritional status-related complications, has been proposed for the evaluation of at-risk elderly patients [1,2,3,4,5,6] and hemodialysis patients [7,8,9,10,11,12], and it was revealed to be a predictor of morbidity and mortality and for the possible use in grading the patient's nutritional status. The relationship between the GNRI and the morbidity of patients with gastrointestinal cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…6 The GNRI has been introduced since 2005 as early screening in patients with malnutrition high risk. 8 Therefore early treatment can be conducted and length of stay, cost, morbidity and mortality can be reduced. This study was conducted to evaluate the relationship of GNRI with length of hospitalization and mortality rate in elderly patients in Dr. Sardjito General Hospital, Yogyakarta…”
Section: Introductionmentioning
confidence: 99%